APLIKASI FORMULA HERBAL STRATEGI PENINGKATAN KUALITAS KESEHATAN SAPI POTONG YANG TERINFEKSI PARASIT SALURAN PENCERNAAN DI KABUPATEN BANGKALAN-MADURA - Hastutiek, Poedji (Jurnal Media Tropika, 2022)
This public service activity aims to share knowledge about herbal formula in a form of dodol temulawak to improve the performance of the cattle infected with gastrointestinal (GI) tract parasite to madura cattle breeder group in Bangkalan Regency. The activities include: counseling about the importance of the gastrointestinal parasitic disease that infecting cattle, identification of the worm eggs and protozoan in cattle stool, training and practice of making dodol temulawak, applicating dodol temulawak for the gastrointestinal parasite-infected cattle, and filling the pretest and post-test was done to ascertain the farmer’s knowledge improvement about the topic and qualitative performance of the infected cattle after the administration of dodol temulawak. The result of the identification indicates that the positive stool sample has Cooperia sp., Oesophagostomum sp., Toxocara sp., Trichuris sp., Capillaria sp., Mecistocirrus sp. eggs, and the protozoan Eimeria sp., Blastocystis sp. The administration of dodol temulawak improves the performance of gastrointestinal parasite-infected cattle, indicated by increased appetite, softer and shiny hair, and a fuller body.